e-Sign: An electronic sign language dictionary (Letters A-M) / Lim Pek San - Lim , Pek San (2005)
e-Sign Dictionary is an electronic sign language dictionary that focused on Malaysian Sign Language. It can be a good learning tool for the deaf community as well as the public in general. e-Sign Dictionary is a trilingual system with instruction in English, Malay and Chinese. Through this system, users will be able to learn not only the sign language of a particular word but also the meaning of the word in English, Malay and Chinese. The synonym and antonym of the word as well as examples of its usage in a sentence are also provided. This system provides three kinds of searching methods that are, search by category, search by alphabetical order and recent search. Most of the words in this system are based on a book named "Belajar Bahasa lsyarat Dalam Sepuluh Jam" (Mr. Tan Yap,1998). The most attractive feature of this system is the animation. Users can view the sign language of a word from different angles. The animation can be rotated 90° to the left or to the right for viewing. In addition, this system also provides "zoom-in" and "zoom-out" features which allow the users to adjust the size of the animation according to their preferences. They can also choose their favourite animated model (i.e. man, woman, boy or girl) to demonstrate the sign language. This system was developed using Visual Basic.Net as the programming language, Microsoft SQL Server for managing databases and 3D Poser 6.0 to create the 3D animations. Besides, it has a function to help the users to learn the pronunciation of the words they are searching. It is hoped that e-Sign Dictionary can bring benefits not only to the deaf community but also to the public at large. In this regard, the primary objective of this system is to foster greater closeness and understanding between the deaf community and the public.